Harmony in Diversity: Social Capital and Social Cohesion in the Gintingan Tradition of the Subang Community - Anwar, Rully Khairul; Khadijah, Ute Lies Siti; Rizal, Edwin (Universitas Andalas, 2023)
This article analyzes a phenomenon found in rural communities in Subang district: the tradition of Gintingan. The Gintingan is a tradition of donating from one family to a family that will or is holding a celebration. Despite modern times, the tradition lives on due to the ownership of society's social capital. By employing a qualitative strategy coupled with a phenomenological technique, this study examines the effects of putting a traditional practice into action. Mutual trust between individuals is crucial in this case, as they exchange goods with each other repeatedly and contribute to helping Sohibul Hajat. Village communities boast a robust social network that serves various common and personal goals. Despite the tradition remaining constant, everything surrounding it transformed, such as invites, track records of attendees, and the design of dinnerware and barbecues, acquiring contemporary sensibilities. Evidently, society adapts to modernity while holding onto tradition.